2004
DOI: 10.3354/meps267241
|View full text |Cite
|
Sign up to set email alerts
|

Sub-populations of coastal cod with different behaviour and life-history strategies

Abstract: This study provides evidence of countergradient variations in life-history traits among coastal cod Gadus morhua off the Norwegian coast, suggesting the existence of sub-populations. One-yr-old wild-caught individuals from 70°N were smaller, grew slower, weighed less, and had a lower condition factor (CF) than southern cod from 60°N during the sampling period from June to February. In contrast, both a higher growth potential and an increase in CF were found in northern cod when offspring of northern and southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 55 publications
(70 reference statements)
7
44
0
2
Order By: Relevance
“…Also, Salvanes et al (2004) documented behavioural differences between sub-groups of juvenile cod farmed in common-garden experiments. The lack of difference between NCC and NEAC in the present study might be related to several conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Salvanes et al (2004) documented behavioural differences between sub-groups of juvenile cod farmed in common-garden experiments. The lack of difference between NCC and NEAC in the present study might be related to several conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that different populations of cod respond differently to temperature and thermal gradients [60][61][62] and, as a population-rich species [63], this population complexity is a key driver in modulating the way that cod populations will respond to environmental change. Integrating this degree of complexity into resource management and climate change models is likely to be a considerable challenge and it may be that simpler but valid generalizations will need to be developed and tested in future field studies.…”
Section: Telemetry and Behaviourmentioning
confidence: 99%
“…This is evidenced by the fact that local adaptation is seen in some oceanic species, such as Atlantic cod (Purchase & Brown 2001, Salvanes et al 2004) and turbot . In some of the oceanic species for which adaptation has been observed, it is possible that dispersal is more limited than in other oceanic fishes (Fairbairn 1981, Grant et al 1984, Diakov 1998, Foss et al 1998, Shulman 1998.…”
Section: Latitudinal Variation In Oceanic Versus Estuarine Speciesmentioning
confidence: 99%
“…For example, Atlantic cod Gadus morhua, displays CnGV in growth patterns similar to those of estuarine silverside fishes (Salvanes et al 2004). Two flatfish species, turbot and halibut, have also been shown to exhibit CnGV in growth , Jonassen et al 2000, and a reef fish, the neon damselfish, was found to show CnGV in egg size and number (Kokita 2003), although in these species mixing may be more limited compared to other oceanic fishes (Fairbairn 1981, Grant et al 1984, Diakov 1998, Foss et al 1998, Shulman 1998.…”
Section: Introductionmentioning
confidence: 99%